Documenting Gaza Under Siege: Strengtening Digital Evidence Standards for Internasional Accountability - Meiske Iriyani; Dendy Prasetyo Nugroho (Bulan Sabit Merah Indonesia, 2026)
The ongoing attacks against civilians in Gaza occur in a closed investigative environment, where access for journalists, humanitarian organizations, and international investigators is systematically restricted due to blockade, infrastructure destruction, and risks of targeted violence. These conditions severely limit the collection of conventional forensic and testimonial evidence, making digital evidence, such as citizen-recorded videos, satellite imagery, communication data, and open-source media, central to documenting alleged violations of international humanitarian law and international criminal law. This paper aims to analyze the role, reliability, and admissibility challenges of digital evidence in efforts to prevent impunity for crimes committed in Gaza. Using a normative legal research method and comparative analysis of international soft law instruments, particularly the Berkeley Protocol on Digital Open Source Investigations and the Leiden Guidelines on Digital Evidence, this study examines how digital documentation may be strengthened to meet evidentiary thresholds applied by the International Criminal Court and United Nations fact-finding mechanisms. The findings indicate that although digital evidence enables continuous documentation under siege conditions, the absence of harmonized standards on authentication, verification, and chain of custody weakens its probative value in judicial proceedings. The paper concludes that harmonizing digital evidence standards from field documentation to courtroom evaluation is essential to ensure that documentation collected in Gaza can meaningfully support accountability processes and contribute to the prevention of impunity.